Temperature distribution in the upper layers of the northern and eastern Arabian Sea during lndo- Soviet monsoon experiment - RAMESHBABU, V.; RAO, L. V. GANGADHARA; VARKEY , M. J; UDAYAVARMA, P. (MAUSAM, 1976)
Scientific cruises were carried out by the ships of the Indian Navy along one zonal section (along 20o N lat.) and one meridional section (along 710 .30 E Long) in the Arabian Sea during May, June and July 1973 under the Indo-Soviet Monsoon Experiment (ISMEX). Using the bathythermograph data collected in these cruises, vertical distribution of temperature in the upper 275 metres was studied. Along the zonal section, east of 670E meridian, the depth of thermocline was found to increase gradually from about 20-30 m in May to 40-50 m in July. Significant fall (of about 10C) in the temperature of the surface water along the meridional section was observed from May to July. Along this section, in July the mixed layer developed well compared to May and the depth of thermocline increased from less than 40 m in the northern part to about 70 m in the southern part.